Normal First Stage of Preterm Labor - Spain, Janine E.; Tuuli, Methodius; Caughey, Aaron B.; Roehl, Kimberly A.; Zhao, Qiuhong; Cahill, Alison G. (American Journal of Perinatology, 2014)
Objective To compare first-stage labor patterns in women in preterm labor to those in labor at term.Study Design We performed a retrospective cohort study of consecutive women admitted from 2004 to 2008 with viable (≥24 weeks) vertex singleton gestations who reached the second stage of labor. Labor curves for preterm and term labor were created using a repeated-measures analysis with polynomial modeling. Interval-censored regression was used to estimate and compare median time of progression of labor. Multivariable analyses were performed to adjust for smoking, obesity (body mass index ≥30), induction, and nulliparity. The adjusted model was stratified by parity and induction of labor.Results Of 5,612 consecutive births, 224 were preterm (<37 weeks) and 5,388 were term (≥37 weeks). Preterm first-stage labor progressed significantly faster than term labor (median time 4 to 10 cm: 3.3 hours versus 4.5 hours, p < 0.01). When stratified by parity, preterm labor progressed significantly more rapidly than term labor in both nulliparous and multiparous women (median time 4 to 10 cm: 3.7 hours versus 4.9 hours [p = 0.04] in nulliparous women and 2.5 hours versus 4.3 hours [p = 0.01] in multiparous women).Conclusion Women in preterm labor progress more rapidly through the first stage of labor than women at term.
Keywords: labor; labor curve; labor dystocia; preterm